Acute disseminated encephalomyelitis - Politi, M; Papanagiotou, P; Grunwald, I; Roth, C; Reith, W (2008)
Acute disseminated encephalomyelitis (ADEM) is an acute widespread autoimmune demyelinating condition, which principally affects the white matter of the brain and spinal cord. It usually follows an infection or vaccination. The typical presentation is that of multifocal neurologic disturbances accompanied by change in mental status. CSF analysis reveals lymphocytic pleocytosis and elevated protein content, but may also yield normal results. MRI is regarded as the diagnostic imaging modality of choice and typically demonstrates involvement of deep cerebral hemispheric and subcortical white matter as well as lesions in the basal ganglia, gray-white junction, diencephalon, brainstem, cerebellum and spinal cord. Unlike multiple sclerosis (MS), ADEM has a monophasic course and a favorable long-term prognosis. © 2008 Springer Medizin Verlag.